A 2D Layered Lanthanide Hydroxide Showing Slow Relaxation of Magnetization – Dy8(OH)20Cl4·6H2O. Issue 29 (9th September 2013) - Monteiro, Bernardo; Pereira, Cláudia C. L.; Coutinho, Joana T.; Pereira, Laura C. J.; Marçalo, Joaquim; Almeida, Manuel
Abstract: The magnetic properties of the layered lanthanide hydroxide Dy8 (OH)20 Cl4 · 6H2 O were studied. Below 5 K, slow magnetic relaxation was observed even in the absence of an external field, with a blocking temperature of 3 K and an energy barrier of 36.1 K, a behavior characteristic of single‐molecule magnets. Abstract : Dy8 (OH)20 Cl4 · 6H2 O, a layered lanthanide hydroxide, shows slow magnetic relaxation at low temperatures with a blocking temperature of 3 K and an energy barrier of 36.1 K, a behavior characteristic of single‐molecule magnets. This is the first example of a layered rare earth compound with such behavior.